Measuring user satisfaction of online web-based support system in International Islamic College (IIC) / Mohamad Kamal Md Dahlan - Md Dahlan, Mohamad Kamal (2005)
With the new information technology and the growth of internet have changed the way user interact. Therefore, it is appropriate to measures end-user satisfaction in web-based environment. The objectives of the research are to measure user satisfaction with online web-based support system in International Islamic College and to validate end user computing satisfaction (EUCS) instruments that proposed by Doll and Torkzadeh (1988).From the study, found that user satisfaction will be affected by working experience factors. In the findings also, noticed that working experience has the most satisfied with online web-based support system. Furthermore, online web-based support system seems not affected by gender and departments. However, there are several issues regarding to web-based environment that can be improved. Privacy and security are the issues that surround online service. Therefore, further research would be needed, as it can be another reason for measuring user satisfaction on the system itself.